Problems of degradation of recreational and environmental areas of the city of kyiv and evaluation biodiversity loses in the context of future integration into eu ecological network natura 2000 - Derkulskyi, R. (Land Management, Cadastre and Land Monitoring, 2017)
Over the past decades the European Union has put in place a broad range of environmental legislation. As a result, air, water and soil pollution has significantly been reduced. Chemicals legislation has been modernised and the use of many toxic or hazardous substances has been restricted. Today, EU citizens enjoy some of the best water quality in the world and over 18% of EU’s territory has been designated as protected areas for nature. On 9 November 2009 under the aegis of Eastern Partnership Platform “Economic Integration and Convergence with the EU Policies” there was established a Panel on the issues of environment and climate change. The Panel facilitates the information and good practices exchange on development and implementation of environmental and climate policies with the aim to promote the approximation of Eastern Partnership countries (includes Ukraine) to the EU legislature in these spheres. The principles of ecological network system in Ukraine and the EU in the context of the EU Directive number 92/43 / EC are analyzed in this article. The necessary preconditions for Ukraine’s ecological network integration to the NATURA 2000 in the future should be: - establishment of Special Protection Areas (SPA’s) on the principles of habitats and species protection; - amendments to legislation of Ukraine in terms of criteria ecological network definition. Biodiversity losses and degradation are identified in recreational and environmental areas of the city of Kyiv. Green areas in Kiev (especially parks) has tendentions of lose their identity because of forest stand changes. The economic value of biodiversity should be factored into decision making in city planning, land management etc. Keywords: biodiversity, ecological network, NATURA 2000, biotope, forest stand, phytocoenosis, herbal layer, landscape and recreational overload.